Effect of NaOH concentration and molar ratios on strength development in geopolymer mortars - Kumar, S. Sundar; Ramesh, G.; Sathik, S.A. Jaffer; Bharatkumar, B.H. (Journal of Structural Engineering, 2024)
In recent year a lot of interest has developed among the civil engineering community regarding geopolymer concrete. Though geopolymer is being discussed as an alternate to Portland cement based concrete, the basic reaction mechanism in both the cases are different. The ingredients that have to be handled in case of geopolymer are more sensitive when compared to cement and water in case of Portland cement based concrete. In the present work experimental studies have been conducted to determine the relation between the Si-Al-Na ratio and the compressive strength of the mix. The studies have been restricted to mortar specimens without any coarse aggregate content. However for one mix ratio Natural River sand has been replaced with copper slag and the strength determined. The end results indicate that there is indeed an optimal Si-Al-Na ratio below which or beyond which strength decreases.